EDITORIAL: The republican factor - Chris Nash (Asia Pacific Network, 2004)
This special edition of Pacific Journalism Review publishes a selection of the papers presented at the Public Right to Know (PR2K) Conference in Sydney in October 2003. The annual PR2K conferences are a project of the Australian Centre for Independent Journalism (ACIJ) at the University of Technology, Sydney. The 2003 conference was the third in the series.